Música comunitária em um projeto social de lazer: processos educativos decorrentes - Arruda, Murilo Ferreira Velho de (2019)
We researched a practice in community music, conducted with children and youth participating in the project Experiences in Diversified Leisure Activities (VADL) in partnership with the project More Than Football (MQF). We aimed to investigate the educational processes of group music making in the community project VADL-MQF, which is based on the actions of Human Motricity (Manuel Sérgio), Existential Phenomenology (Maurice Merleau-Ponty), Ecology of Knowledges (Boaventura de Sousa Santos) and Dialogical Pedagogy (Paulo Freire). We had twenty-three meetings: twenty-one days between March 13 and June 7, 2018, when we first presented the idea and built a collective musical practice to play percussion instruments, and did appreciation, movement and score reading activities; a meeting on June 10, 2018, related to a conversation circle and musical performance with family members, participants and educators; and a meeting on September 22, 2019, when we re-encountered participants, family members and educators to talk about data analysis. Opting for a qualitative research with phenomenological approach to data collection and analysis, all these meetings had audiovisual recordings enabling a rigorous transcription of the speeches of participants. The diaries have descriptive and reflective elements. About the analysis, we first identified and highlighted the meaning units, a moment called ideographic analysis, to later group these units by thematic proximity. With this nomothetic analysis, we come to the following categories: A) “Let's go to music, right? Because this is my strength!”- Knowing and acknowledging each other; B) “Oh, I will teach you, ok? First we start here and then we go here”- Teaching and learning from each other; C) “Right on!” - Choosing and matching. The findings are related to educational processes related to the recognition of others through musical practice, autonomy of acting and teaching and democratic experience were highlighted.